Integrative proteomics and immunochemistry analysis of the factors in the necrosis and repair in acetaminophen‐induced acute liver injury in mice. Issue 5 (11th November 2018) - Feng, Qin; Zhao, Ningwei; Xia, Wenkai; Liang, ChengJie; Dai, Guoxin; Yang, Jian; Sun, Jingxia; Liu, Lanying; Luo, Lan; Yang, Jie
Abstract: Acetaminophen (APAP) overdose‐induced acute liver injury (AILI) is a significant clinical problem worldwide, the hepatotoxicity mechanisms are well elucidated, but the factors involved in the necrosis and repair still remain to be investigated. APAP was injected intraperitoneally in male Institute of Cancer Research (ICR) mice. Quantitative proteome analysis of liver tissues was performed by 2‐nitrobenzenesulfenyl tagging, two‐dimensional‐nano high‐performance liquid chromatography separation, and matrix‐assisted laser desorption/ionization–time of flight mass spectrometry analysis. Diffrenetial proteins were verified by the immunochemistry method. 36 and 44 differentially expressed proteins were identified, respectively, at 24 hr after APAP (200 or 300 mg·kg −1 ) administration. The decrease in the mitochondrial protective proteins Prdx6, Prdx3, and Aldh2 accounted for the accumulation of excessive reactive oxygen species (ROS) and aldehydes, impairing mitochondria structure and function. The Gzmf combined with Bax and Apaf‐1 jointly contributed to the necrosis. The blockage of Stat3 activation led to the overexpression of unphosphorylated Stat3 and the overproduction of Bax. The overexpression of unphosphorylated Stat3 represented necrosis; the alternation from Stat3 to p‐Stat3 in necrotic regions represented hepatocytes from death to renewal. The high expressions of P4hα1, Ncam, α‐SMA, and Cygb were involved in the liver repair, they were not only the markers of activated HSC but also represented an intermediate stage of hepatocytes from damage or necrosis to renewal. Our data provided a comprehensive report on the profile and dynamic changes of the liver proteins in AILI; the involvement of Gzmf and the role of Stat3 in necrosis were revealed; and the role of hepatocyte in liver self‐repair was well clarified. Abstract : Our data provided a comprehensive report on the profile and dynamic changes of the liver proteins in AILI; the involvement of Gzmf and the role of Stat3 in necrosis were revealed; and the role of hepatocyte in liver self‐repair was well clarified.